70th meeting of the American Chemical Society, August, 1925 - American Chemical Society (1925)
Panoramic photograph of the Members of the American Chemical Society (ACS) at the 70th national convention, hosted by the Southern California Section of ACS. The picture was taken at the "Avocado Luncheon" at Queen Walker Boardman's (1881-1954) home in West Hollywood, California. The event was hosted by Dr. Willett Lepley Hardin (1868-1960) and Mrs. W. L. Hardin, and the Avocado Growers Association of Southern California.
Keywords: Congresses and conventions; American Chemical Society; Photography, Panoramic